2017
DOI: 10.1016/j.quaint.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

An ethnoarchaeological study of livestock dung fuels from cooking installations in northern Tunisia

Abstract: Livestock dung is a valuable material in many rural communities worldwide. In our research area, the site of Althiburos and its surroundings, now el Médéïna, in northwestern Tunisia, dung is the main source of fuel for domestic purposes, primarily the processing and cooking of foods. Ovicaprine dung is daily used in traditional mud tannur type ovens, namely tabouna. The archaeological record shows that mud constructed cooking installations were common during the first millennium BC. Previous studies of phytoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…These are suggested to derive from ruminant faecal matter, particularly ovicaprines, as faunal remains from this site include a substantial proportion of herded sheep (Baird et al 2011). In addition, modern reference livestock dung datasets from Mediterranean areas have demonstrated that sheep and goats are prolific producers of dung spherulites (Portillo, Valenzuela, and Albert 2012;Portillo et al 2014;Portillo et al 2017). The dominant morphotypes in this assemblage are individual or single-celled phytoliths, mainly epidermal short cells, which are produced in the leaves, culms, and inflorescences of grasses.…”
Section: Microfossil Variations By Contextmentioning
confidence: 92%
See 2 more Smart Citations
“…These are suggested to derive from ruminant faecal matter, particularly ovicaprines, as faunal remains from this site include a substantial proportion of herded sheep (Baird et al 2011). In addition, modern reference livestock dung datasets from Mediterranean areas have demonstrated that sheep and goats are prolific producers of dung spherulites (Portillo, Valenzuela, and Albert 2012;Portillo et al 2014;Portillo et al 2017). The dominant morphotypes in this assemblage are individual or single-celled phytoliths, mainly epidermal short cells, which are produced in the leaves, culms, and inflorescences of grasses.…”
Section: Microfossil Variations By Contextmentioning
confidence: 92%
“…The methods used in this study are similar to those proposed by Canti (1999). Portillo et al 2014Portillo et al , 2017Tsartsidou et al 2008).…”
Section: Dung Spherulite Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Temperatures as high as 850°C were reached within a few minutes after lighting in modern traditional mud ovens operated with dung-dominated fuels, as reported in geoethnoarchaeological studies from different geographical regions (Gur-Arieh et al 2013;Portillo et al 2014Portillo et al , 2017. Dung fuels can sustain temperatures for longer than wood sources, remaining hot several hours after the end of the activity (e.g.…”
Section: Dung Burning and The Use Of Dung In Construction Materialsmentioning
confidence: 56%
“…Comparative geo-ethnoarchaeological and experimental research on dung assemblages provides an important framework for examining the significance of dung indicators and their contextual associations, as well as the ecological and anthropogenic factors influencing these (e.g. Brochier et al 1992;Canti 1999;Shahack-Gross et al 2003Macphail et al 2004;Milek 2012;Portillo et al 2014Portillo et al , 2017Elliott et al 2015;Friesem 2016;Prost et al 2017;Égüez et al 2018).…”
Section: Introductionmentioning
confidence: 99%